(untitled) (LAPAI JOURNAL OF NIGERIA HISTORY, 2023)
This study explores how historical legacies, political transitions, and technological advancements have shaped the landscape of public administration in Nigeria. It examines the historical evolution of e-governance in Nigeria, tracing its development from the pre-independence era to the present day. Drawing on historical analysis and theoretical frameworks such as Institutional Theory and the Technology Acceptance Model (TAM), the research explores the key milestones, challenges, and opportunities that have shaped Nigeria’s journey towards digital governance. Through a comprehensive review of literature and historical analysis, the study highlights the impact of colonial legacies, political transitions, and technological advancements on the adoption and implementation of e-governance initiatives. The findings underscore the importance of understanding historical contexts in shaping contemporary e-governance strategies and offer insights for policymakers and practitioners seeking to enhance digital governance in Nigeria.